Recommendation For Higher Education Destination: What Matters? - Ismail, Russayani; Chuan, Chew Foo; Ibrahim, Yusnidah; Sabudin, Noor Sa'adah (2016)
The internationalisation of higher education seems to preoccupy the agenda for globalisation with free mobilisation of students across borders. 'Student hub' is now becoming a common term to many and there are increasing numbers of emerging economies competing for international students focusing on income generation. The ability of a host country to attract the international students depends on many factors, and recommendations or reviews by friends or families who are currently study or had experience studied in a particular host country found to be an effective marketing tool. Based on the data of 753 international students, gathered from a sample of few universities in Malaysia, this particular study employs a Logit Model in an attempt to identify the factors that affect the decision of the currently enrolled international students to recommend Malaysia as a study destination to their friends and families. The result shows that the university environment, university service, academic quality and social factor affect the decision of the international students to recommend Malaysia. This outcome is consistent with other previous studies who found that the quality of services provided by the host country in general and university in particular, level of discrimination and education cost influence individuals willingness to recommend the host nation to their peers. Interestingly, while education cost matters, it however shows the positive relationship between cost and the tendency to recommend Malaysia as higher education destination, thus signifies that higher cost reflect quality.